Safety of Herbal Products in Thailand: An Analysis of Reports in the Thai Health Product Vigilance Center Database from 2000 to 2008 - Saokaew, Surasak; Suwankesawong, Wimon; Permsuwan, Unchalee; Chaiyakunapruk, Nathorn (Drug safety, 2011)
Background: The use of herbal products continues to expand rapidly across the world and concerns regarding the safety of these products have been raised. In Thailand, Thai Vigibase, developed by the Health Product Vigilance Center (HPVC) under the Thai Food and Drug Administration, is the national database that collates reports from health product surveillance systems and programmes. Thai Vigibase can be used to identify signals of adverse events in patients receiving herbal products. Objectives: The purpose of the study was to describe the characteristics of reported adverse events in patients receiving herbal products in Thailand. Methods: Thai Vigibase data from February 2000 to December 2008 involving adverse events reported in association with herbal products were used. This database includes case reports submitted through the spontaneous reporting system and intensive monitoring programmes. Under the spontaneous reporting system, adverse event reports are collected nationwide via a national network of 22 regional centres covering more than 800 public and private hospitals, and health service centres. An intensive monitoring programme was also conducted to monitor the five single herbal products listed in the Thai National List of Essential Medicines (NLEM), while another intensive monitoring programme was developed to monitor the four single herbal products that were under consideration for inclusion in the NLEM. The database contained patient demographics, adverse events associated with herbal products, and details on seriousness, causality and quality of reports. Descriptive statistics were used for data analyses. Results: A total of 593 reports with 1868 adverse events involving 24 different products were made during the study period. The age range of individuals was 1–86 years (mean 47 years). Most case reports were obtained from the intensive monitoring programme. Of the reports, 72% involved females. The herbal products for which adverse events were frequently reported were products containing turmeric (44%), followed by andrographis (10%), veld grape (10%), pennywort (7%), plai (6%), jewel vine (6%), bitter melon (5%) and snake plant (5%). Gastrointestinal problems were the most common adverse effect reported. Serious adverse events included Stevens-Johnson syndrome, anaphylactic shock and exfoliative dermatitis. Conclusions: Adverse event reports on herbals products were diverse, with most of them being reported through intensive monitoring programmes. Thai Vigibase is a potentially effective data source for signal detection of adverse events associated with herbal products.